High-Risk Youth and Their Families: A Qualitative Needs Assessment - Agaskar, Vaibhavee R. (Journal of addictions & offender counseling, 2020)
This qualitative study of 36 high-risk youth and their families identified the need for educational/career services, high quality after-school programs, behavioral health and social services, safety and violence interventions, sports/recreational activities, and sex education.